答案1
以下是实现此目的的简单方法:
\documentclass{article}
\usepackage{amsmath,amstext}
\usepackage{newtxmath}
\begin{document}
\begin{equation}
\begin{cases}
\displaystyle
\nu(z_0)+\frac{g}{f}\frac{\partial\,\eta_s}{\partial\,x}
=\frac{g}{f}\frac{\partial\,\eta}{\partial\,x}\\[15pt]
\displaystyle\text{with }\nu(z_0) =
\frac{1}{f\rho_0}\frac{\partial\,P_{z0}}{\partial\,x}
\end{cases}
\Rightarrow \eta = \eta_s+ \frac{P_{z0}}{\rho_0g}
\end{equation}
\end{document}
输出:
答案2
使用amsmath
\documentclass{article}
\usepackage{amsmath}
\begin{document}
If you want it center-aligned inside the braces, use \texttt{gathered}
\begin{equation}
\left\{
\begin{gathered}
v(z_0) + \frac{g}{f} \frac{\partial\eta_s}{\partial x} = \frac{g}{f} \frac{\partial \eta}{\partial x} \\
\text{with } v(z_0) = \frac{1}{f\rho_0} \frac{\partial P_{z0}}{\partial x} \text{ (junk to show alignment)}
\end{gathered}
\right. \implies \eta = \eta_s + \frac{P_{z0}}{\rho_0 g}
\end{equation}
If you want it either left-aligned, it is slightly simpler:
\begin{equation}
\begin{cases}
v(z_0) + \frac{g}{f} \frac{\partial\eta_s}{\partial x} = \frac{g}{f} \frac{\partial \eta}{\partial x} \\
\text{with } v(z_0) = \frac{1}{f\rho_0} \frac{\partial P_{z0}}{\partial x} \text{ (junk to show alignment)}
\end{cases}
\implies \eta = \eta_s + \frac{P_{z0}}{\rho_0 g}
\end{equation}
If for some reason you want it right aligned, you can use \texttt{aligned}
\begin{equation}
\left\{
\begin{aligned}
v(z_0) + \frac{g}{f} \frac{\partial\eta_s}{\partial x} = \frac{g}{f} \frac{\partial \eta}{\partial x} \\
\text{with } v(z_0) = \frac{1}{f\rho_0} \frac{\partial P_{z0}}{\partial x} \text{ (junk to show alignment)}
\end{aligned}
\right. \implies \eta = \eta_s + \frac{P_{z0}}{\rho_0 g}
\end{equation}
\end{document}
答案3
我会这样做,使用中的dcases
和rcases
环境mathtools
。此外,该esdiff
包简化了 (部分) 导数的输入。
\documentclass{article}
\usepackage{mathtools}
\usepackage{fourier, erewhon}
\usepackage{esdiff}
\begin{document}
\begin{equation}
\begin{rcases}\begin{dcases}
ν(z₀)+\frac{g}{f}\diffp{\eta_s}{x}
=\frac{g}{f}\diffp{η}{x}\\[0.5ex]
\text{with }ν(z₀) =
\frac{1}{f\rho₀}\diffp{P_{z0}}{x}
\end{dcases}\end{rcases}
⇒ η= \eta_s+ \frac{P_{z0}}{\rho₀g}
\end{equation}
\end{document}